2022
DOI: 10.32604/phyton.2022.018321
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Improvement in Juglans mandshurica and Its Uses in China: Current Status and Future Prospects

Abstract: Juglans mandshurica is an economically and ecologically valuable species that is used for various construction purposes, making luxurious furniture, as food and sources of medicinal substances and landscaping because of its excellent wood, edible fruits and rich in various types of chemical compounds. In the past few decades, several genetic improvements of J. mandshurica were made, with a focus on the selection of improved varieties and on breeding technology. Many elite provenances and families were selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 87 publications
0
4
0
Order By: Relevance
“…Previous reports have shown that AP2/ERF TFs can be potential candidates for plant improvement because they are key regulators in different plant development processes and various stress responses [ 12 ]. In J. mandshurica , female flower buds, male flower buds, and phloem tissues are the main overwintering organs with strong cold resistance [ 26 ]. In this study, we used these tissues to perform cold stress treatment with different gradients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous reports have shown that AP2/ERF TFs can be potential candidates for plant improvement because they are key regulators in different plant development processes and various stress responses [ 12 ]. In J. mandshurica , female flower buds, male flower buds, and phloem tissues are the main overwintering organs with strong cold resistance [ 26 ]. In this study, we used these tissues to perform cold stress treatment with different gradients.…”
Section: Discussionmentioning
confidence: 99%
“…The species is widely distributed throughout cold regions of China, South Korea, Japan, and Russia [ 25 ]. J. mandshurica is a good timber tree species due to of its hard and dense material and good elasticity [ 26 ]. The rich nutrition and high oil content in the fruit kernel of J. mandshurica can be used to make oil and health food.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…is a perennial woody species, with economic and ecological value. The distribution of J. mandshurica is in Japan, North Korea, the Russian Far East, and northeast China [ 31 , 32 ]. In particular, it possesses the characteristics of multipurpose components, long life, and heterodichogamy.…”
Section: Introductionmentioning
confidence: 99%